INFLUENCE OF SERVICE QUALITY AND FARE TOWARD CUSTOMER SATISFACTION AND ITS IMPACT ON CUSTOMER LOYALTY OF EXPRESS TAXI IN JAKARTA - Rizan, Mohammad; Fadillah, Erwin; Kresnamurti R. P., Agung (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2015)
The purpose of this study was to: to examine empirically the effect of service quality to customer satisfaction on Express taxi, to examine empirically the effect of fare to customer satisfaction on Express taxi, to examine empirically the effect of customer satisfaction to customer loyalty on Express taxi, to examine empirically the effect of service quality to customer loyalty on Express taxi, and to examine empirically the effect of fare to customer loyalty on Express taxi. Data collection using survey methods. Sample of this study are 200 respondents who have using services of Express taxi more than two times in last three months. Data analysis using SPSS version 23 and SEM (Structural Equation Modeling) LISREL version 8.7. Results of hypothesis testing showed: service quality have positive and significant effect on customer satisfaction, fare have positive and significant effect on customer satisfaction, customer satisfaction have positive and significant effect on customer loyalty, service quality have positive and not significant effect to on customer loyalty. fare have positive and significant effect to on customer loyalty. Rated fit model with value of RMSEA 0.043, value of RMR 0.043, value of CMIN/DF 1.88, value of NFI 0.96, value of NNFI 0.98, and value of CFI 0.98. The results of this research beneficial to transportation company, especially Express taxi in Jakarta, to create better strategy in improving customer loyalty. Keywords: service quality, fare, customer satisfaction, customer loyalty, transportation